Ethylene Response Factor Sl-ERF.B.3 Is Responsive to Abiotic Stresses and Mediates Salt and Cold Stress Response Regulation in Tomato. (6th August 2014) - Klay, Imen; Pirrello, Julien; Riahi, Leila; Bernadac, Anne; Cherif, Ameur; Bouzayen, Mondher; Bouzid, Sadok
Abstract : Sl-ERF.B.3 (Solanum lycopersicum ethylene response factor B.3) gene encodes for a tomato transcription factor of the ERF (ethylene responsive factor) family. Our results of real-time RT-PCR showed that Sl-ERF.B.3 is an abiotic stress responsive gene, which is induced by cold, heat, and flooding, but downregulated by salinity and drought. To get more insight into the role of Sl-ERF.B.3 in plant response to separate salinity and cold, a comparative study between wild type and two Sl-ERF.B.3 antisense transgenic tomato lines was achieved. Compared with wild type, Sl-ERF.B.3 antisense transgenic plants exhibited a salt stress dependent growth inhibition. This inhibition was significantly enhanced in shoots but reduced in roots, leading to an increased root to shoot ratio. Furthermore, the cold stress essay clearly revealed that introducing antisense Sl-ERF.B.3 in transgenic tomato plants reduces their cell injury and enhances their tolerance against 14 d of cold stress. All these results suggest that Sl-ERF.B.3 gene is involved in plant response to abiotic stresses and may play a role in the layout of stress symptoms under cold stress and in growth regulation under salinity.